2021
DOI: 10.1016/j.childyouth.2020.105784
|View full text |Cite
|
Sign up to set email alerts
|

Public knowledge, attitudes, and practices towards COVID-19 in Pakistan: A cross-sectional study

Abstract: Highlights It is an attempt to understand the mechanism that is crucial to predict the success of COVID-19 management policies. First, we investigate the level of knowledge and awareness of COVID-19 among university students and graduates. Second, we examine the attitudes and confidence of them in the success of the COVID-19 management policy. The results suggest an urgent need for health education programs to hold optimistic attitudes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 12 publications
7
33
1
6
Order By: Relevance
“…More than 90% of participants agreed that COVID-19 will be successfully controlled and believed that Indonesia can win against COVID-19. These results are similar to those of previous studies conducted in Indonesia [ 23 ] and elsewhere [ 26 , 42 , 48 , 49 , 50 ]. These results indicated that although COVID-19 has spread worldwide, most people had an optimistic attitude; they believed that the COVID-19 pandemic will end and that their countries will win against this pandemic.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…More than 90% of participants agreed that COVID-19 will be successfully controlled and believed that Indonesia can win against COVID-19. These results are similar to those of previous studies conducted in Indonesia [ 23 ] and elsewhere [ 26 , 42 , 48 , 49 , 50 ]. These results indicated that although COVID-19 has spread worldwide, most people had an optimistic attitude; they believed that the COVID-19 pandemic will end and that their countries will win against this pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…Among demographic characteristics, sex was significantly associated with the attitude that COVID-19 will be successfully controlled, and Indonesia can win the battle against COVID-19 ( Table 2 ). Similarly, a previous study reported that sex was significantly associated with attitude [ 49 ]. Moreover, higher knowledge scores were significantly associated with the positive attitude that COVID-19 will be successfully controlled.…”
Section: Discussionmentioning
confidence: 81%
“…Beberapa penelitian lain menunjukkan bahwa pandemi covid-19 membuat masyarakat menjadi menutup diri dari lingkungan bahkan menjadi paranoid, kecemasan masyarakat (Lopes et al, 2021;Roy et al, 2020;Kowalski et al, 2020). Beberapa penelitian mengenai stigma masyarakat yang lahir dari pengetahuan terhadap pasien covid telah dilakukan (Xue, 2021;Roy et al, 2020., Iqbal., 2021. Di Indonesia beberapa penelitian telah dilakukan namun hanya di daerah Indonesia Barat (Saefi et al, 2020;Rahman et al, 2020;Bela et al, 2021).…”
Section: Pendahuluanunclassified
“…Furthermore, it spreads from one person to another through nasal exhales (sneeze and cough), physical contact, point of contact i. e, handshakes, hugs, and mutual connection of surfaces (WHO, 2020b and Iqbal et al, 2020). In the first wave of COVID-19, Pakistan, through the smart lockdown and Vector Autoregressive model (see Iqbal and Younas, 2021;Khan et al, 2020; for more details), controlled the increasing coronavirus cases and decreased patients from 6604 (see Figure 2) to a few hundred. The efforts made by the Government of Pakistan were appreciated by other countries, especially from the World Health Organization (WHO, 2020), yet; the same govt showed negligence and sluggishness being relaxed.…”
Section: Figure 1: Covid-19 History In Pakistanmentioning
confidence: 99%